1593. Recurrence of Clostridium difficile Infection in Multiple Myeloma Patients Receiving Prophylactic Oral Vancomycin or Oral Metronidazole vs. No Prophylaxis. (26th November 2018) - Moran, Gisele; Yarlagadda, Naveen; Susanibar, Sandra; Kothari, Atul; Rico, Juan Carlos; Burgess, Mary J
Abstract: Background: Multiple myeloma (MM) patients are at increased risk of Clostridium difficile infection (CDI) compared with the general population. In prior studies, 12–14% were diagnosed with CDI, and ~16% had recurrent CDI during subsequent treatments. Recent studies have shown that oral vancomycin is effective secondary prophylaxis for the prevention of recurrent CDI in the general population. This retrospective study examined if secondary prophylaxis with oral vancomycin or metronidazole is effective to prevent recurrent CDI in MM patients. Methods: MM patients who tested positive for their first episode of CDI from January 2014–December 2016 were included, and the 3 months following the CDI diagnosis was reviewed. Patients who died, and those who did not receive additional chemotherapy or antibiotics during the 3-month review period were excluded. The patients were divided into 3 cohorts: (1) oral vancomycin as secondary prophylaxis, (2) oral metronidazole as secondary prophylaxis, and (3) no C. difficile prophylaxis. Results: A total of 110 MM patients with a first episode of CDI were reviewed, six were excluded due to death and four were excluded due to no subsequent chemotherapy or antibiotics. This left 100 patients included for analysis. The median age was 62 years, range 34–81. 92 subjects (92%) had exposure to antibiotics and 76 (76%) received chemotherapy. A total of 38 (38%) received secondary prophylaxis: 16 (42%) with oral metronidazole and 22 (58%) with oral vancomycin. There was no significant difference in recurrent CDI in patients who received any secondary prophylaxis (7/38, 18.4%) and in those who received none (15/62, 24.2%), P = 0.46. Incidence of recurrent CDI in patients receiving oral vancomycin (3/22, 13.6%) was not significantly different from patients receiving oral metronidazole (4/16, 25%), P = 0.56. An analysis of risk factors for recurrent CDI showed no difference in recurrence in patients who received metronidazole vs. vancomycin as treatment for the initial CDI. Similar recurrent CDI occurred in patients who received antibiotics and those who received chemotherapy. Conclusion: Secondary prophylaxis with either oral metronidazole or oral vancomycin did not reduce the incidence of recurrent CDI in MM patients. Disclosures: All authors: No reported disclosures.